National social attitudes and political appeals in the process of rising of competitive sports in China - Shengfang, S.; Mina, W. (International Journal of Human Movement and Sports Sciences, 2016)
There are three developing phases of Chinese competitive sports in term of national social attitudes and political appeals in the past sixty years. In the first 30 years, reluctance to show weakness or suffering disgrace reflected social attitudes, while the political appeals were to promote the national prestige, to wash off the shame of "Sick Man of East Asia" and to gain the international dignity in the worldwide playing fields; In the latter 30 years, the social attitudes appeared as the rising of nationalist sentiment, while the political appeals were to "bring about a great rejuvenation of the Chinese nation with the Olympic success". Since the Beijing Olympics, the national social attitude diversified while the Gold Medal became not as important as before. And the political appeals were the pursuit of "Harmonious World".